Optimal Payments to Connected Depositors in Turbulent Times: A Markov Chain Approach - Dávid Csercsik; Hubert János Kiss (Complexity)
We propose a discrete time probabilistic model of depositor behavior which takes into account the information flow among depositors. In each time period each depositors’ current state is determined in a stochastic way, based on their previous state, the state of other connected depositors, and the strategy of the bank. The bank offers payment to impatient depositors (those who want to withdraw their funds) who accept or decline them with certain probability, depending on the offered amount. Our principal aim is to see what are the optimal offers of the bank if it wants to keep the expected chance of a bank run under a certain level and minimize its expected payments, while taking into account the connection structure of the depositors. We show that in the case of the proposed model this question results in a nonlinear optimization problem with nonlinear constraints and that the method is capable of accounting for time-varying resource limits of the bank. Optimal offers increase (a) in the degree of the depositor, (b) in the probability of being hit by a liquidity shock, and (c) in the effect of a neighboring impatient depositor.